The Influence Of Human Resources Competency In The Utilization Of Simrs In Bandung General Hospital Medan City - Sapriadi, Sapriadi; Khairaniswah, Khairaniswah; Khairatunnisa, Khairatunnisa (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Hospital management information systems Implementation is believed to provide various benefits for health service providers. Therefore, human resources need to be empowered and supported in terms of developing services in the health sector based on technology. To determine the effect of HR competence in the utilization of hospital management information systems at Bandung General Hospital, Medan City. The research is an analytical survey with cross sectional. The population used was all human resources at Bandung Hospital, Medan City, totaling 141 people and sampling using simple random sampling so that 59 people were found. Data analysis using univariate and bivariate tests (chi square test0. There is an influence of HR work skills (p=0.002), HR knowledge (p=0.005), HR work experience (p=0.005) and HR work behavior (p=0.007) on the use of hospital management information systems. There is an influence of HR work skills, HR knowledge, HR work experience and HR work behavior on the utilization of hospital management information systems at Bandung General Hospital, Medan City. It is expected that hospitals can conduct training or socialization regularly to improve knowledge and quality of health services.